SOC 2018 - Witt, John (McGraw Hill, 2018)
Connect also comes with LearnSmart, an adaptive questioning tool proven to increase content comprehension and student results, as well as fun interactivities like In their Shoes and Applying the Perspectives that teach sociology's three theoretical frameworks.